Audit Sistem Keamanan Jaringan Pada PT TRIAS SENTOSA TBK - Michael Setiono; Leo Willyanto Santoso; Agustinus Noertjahyana (Jurnal Infra, 2016)
PT Trias Sentosa was founded in 1979. The company is dealing with manufacturing and production of plastics, During the last year to date, PT. Trias Sentosa Tbk has used a security system that is highly controlled and has been tested kelayakanya communication between each warehouse to a central server. However, sometimes the data from BOPPET that go into servers sometimes experience an error or what is often called